Análisis crítico de la política criminal y del tipo de injusto del delito fiscal en el perú - Yon Ruesta, Roger; Sánchez-Málaga Carrillo, Armando (Pontificia Universidad Católica del Perú, 2013)
In Peru, successive governments have designed their tax collection policy on the basis of the formal sector without addressing the issue of the informal sector, because of the lack of a plan on criminal tax policy. However, this creates a problem of regularization of tax and criminal policy and a space for the commission of tax offenses. In the present article, the authors do research about the subject, noting that when legislators create incentives for the management of economic strategies, it produces an undesirable effect: it creates room for unfair tax crime. Therefore, we should seek to analyze the political-criminal aspects of the offenses listed above, based on a study of the work of the criminal law on taxation.

En el Perú, los diferentes gobiernos de turno han diseñado su política recaudatoria sobre la base del sector formal sin abordar la temática del informal, debido a que no ha existido –ni existe– un plan de política penal tributaria. Esta carencia genera un problema de regularizaciónde la política fiscal y criminal, dejando un espacio para la comisión de delitos fiscales. En este artículo, los autores investigan la problemática señalando que la creación de incentivos para la realización de estrategias económicas por parte de los legisladores producirá un efecto inverso al deseado: El tipo injusto del delito fiscal. Por ello, se buscará analizar adecuadamente los aspectos político-criminales de los delitos mencionados anteriormente en el marco del Derecho Penal Tributario.
Keywords: Law; Criminal Policy; Tax Crime; Criminal Tax Policy; Regularization; Incentives; Tax Fraud; Política criminal; Delito fiscal; Política penal tributaria; Regularización; Incentivos; Defraudación tributaria; https://purl.org/pe-repo/ocde/ford#5.05.01